ZPrivacy Suite: Android Based Permission Manager Incorporated with Firewall Technology - Mon Sharif, Siti Zulaiha; Abdullah, Dalilah (Journal of Computing Technologies and Creative Content, 2019)
The user privacy security is one of the major concern, especially in IT world today. With user’s information, nasty user especially hacker can do lots of malicious activity, for example, identity theft, spam, social engineering and lots more which will harm the user. The main purpose of this project is to monitor and protect the android user from privacy leak while solving the default android problem, Take-it-or-Leave-it policy on Android platform running version 5.0 and below. In addition, the powerful Linux firewall, IPtables, also has been embedded as an extra layer of security which functions to reject unwanted or unnecessary internet access requested by the application which in return benefits the user to reduce the usage of mobile data and at the same time increase the battery life. ZPrivacy Suite: An Android-based permission manager incorporated with firewall technology were developed as a solution to the problem arise.